2020
DOI: 10.3390/biom10010069
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12b Enhances the Cytotoxicity of Diethyldithiocarbamate in a Synergistic Manner, Inducing the Paraptosis-Like Death of Human Larynx Carcinoma Cells

Abstract: We have shown that hydroxycobalamin (vitamin B12b) increases the toxicity of diethyldithiocarbamate (DDC) to tumor cells by catalyzing the formation of disulfiram (DSF) oxi-derivatives. The purpose of this study was to elucidate the mechanism of tumor cell death induced by the combination DDC + B12b. It was found that cell death induced by DDC + B12b differed from apoptosis, autophagy, and necrosis. During the initiation of cell death, numerous vacuoles formed from ER cisterns in the cytoplasm, and cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
5
15
0
Order By: Relevance
“…Probably, ROS formed during the oxidation of DDC rapidly transform to reactive sulfur species. This could explain a partial inhibition of the cytotoxic effect of the combination of DDC with H2OCbl + /HOCbl by catalase, which was observed here and earlier [39,51]. The absence of any influence of CNCbl on the DDC-induced cell death as well as the absence of CL during the oxidation of DDC in the presence of CNCbl may be due to a slow oxidation of this compound.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Probably, ROS formed during the oxidation of DDC rapidly transform to reactive sulfur species. This could explain a partial inhibition of the cytotoxic effect of the combination of DDC with H2OCbl + /HOCbl by catalase, which was observed here and earlier [39,51]. The absence of any influence of CNCbl on the DDC-induced cell death as well as the absence of CL during the oxidation of DDC in the presence of CNCbl may be due to a slow oxidation of this compound.…”
Section: Discussionsupporting
confidence: 73%
“…Our previous results have indicated that combinations of HOCbl with GSH, NAC, AA [31], DTT [32], and DDC [38,39,51] produce a cytotoxic effect on HEp-2 cells. It was shown using an oxygen electrode that the oxidation of thiols [31,32] and AA [31] catalyzed by H2OCbl + /HOCbl is accompanied by the accumulation of hydrogen peroxide in culture medium.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, it was shown that vitamin B12 contributes to a distinctive mechanism of cell death known as paraptosis-like cell death. The combination of vitamin B12 with diethyldithiocarbamate stimulated disulfiram oxiderivatives formation resulting in severe ER stress and extensive ER vacuolization leading to paraptosis-like cell death [35]. Moreover, a study done on HL-60 human lymphocytic leukemia cell line showed that the use of vitamin B12 in combination with thiol antioxidants such as dithiothreitol (DTT), glutathione, and N-acetylcysteine resulted in lysosome dysfunction followed by apoptosis [36].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous results indicate that combinations of HOCbl with GSH, NAC, DTT, and ascorbic acid (AA) lead to apoptotic death in cancer cells [ 31 , 32 , 37 ]. At the same time, a combination of HOCbl with sodium diethyldithiocarbamate (DDC) leads to entosis [ 38 ] and/or paraptosis-like cell death [ 38 , 39 ]. For a more complete understanding of mechanisms underlying the effects of cobalamin-reducing agent combinations, a deeper insight into ongoing chemical processes is needed.…”
Section: Introductionmentioning
confidence: 99%